2008
DOI: 10.1139/h08-102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xanthine oxidase inhibition on oxidative stress and swimming performance in rats

Abstract: The aim of this study was to examine the effect of allopurinol, a xanthine oxidase inhibitor, on oxidative stress and physical performance after swimming until exhaustion in rats. Blood and gastrocnemius muscle samples were collected before, immediately after, and 5 h after exercise and the respective timepoints after allopurinol administration. Xanthine oxidase and total antioxidant capacity (TAC) were determined in plasma and muscle, whereas catalase activity and reduced (GSH) and oxidized (GSSG) glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 43 publications
7
60
1
8
Order By: Relevance
“…Accordingly, it has been demonstrated that swimming exercise increases the levels of most of the oxidative stress markers in muscle. 36 In view of the results obtained, we propose that the increase of NPSH and ascorbic acid levels demonstrated in this study occurred as an adaptive response of muscle tissue to lipid peroxidation. It is well documented that during conditions of oxidative stress, such as exercise, increased circulation of antioxidants may result from an increased release from tissue pools, in turn sparing the quenching of other components of the antioxidant defense system.…”
Section: Discussionsupporting
confidence: 54%
“…Accordingly, it has been demonstrated that swimming exercise increases the levels of most of the oxidative stress markers in muscle. 36 In view of the results obtained, we propose that the increase of NPSH and ascorbic acid levels demonstrated in this study occurred as an adaptive response of muscle tissue to lipid peroxidation. It is well documented that during conditions of oxidative stress, such as exercise, increased circulation of antioxidants may result from an increased release from tissue pools, in turn sparing the quenching of other components of the antioxidant defense system.…”
Section: Discussionsupporting
confidence: 54%
“…Blood flow redistribution during exercise is a well-known adaptation in exercise physiology and describes the vasodilation of the vascular system of the active muscle and the vasoconstriction of the vasculature of the non-active muscle tissue. The hypoxic nonactive tissue receives a greater quantity of blood after exercise and enhanced formation of RONS is possible due to the xanthine oxidase mechanism (Finaud et al 2006; Veskoukis et al 2008). This mechanism of RONS production seems also unlikely to account for the increased oxidative stress that appears days following eccentrically-induced muscle damage.…”
Section: Eccentric Exercise Oxidative Stress and Muscle Damagementioning
confidence: 99%
“…Treadmill exercise has been associated with the increased generation of reactive oxygen species (ROS) in skeletal muscle (4,5). Many reports also suggest that exercise-induced ROS production is responsible for the activation of signaling pathways in skeletal muscle that will culminate in cellular adaptation to exercise (6,7).…”
Section: Introductionmentioning
confidence: 99%